2001
DOI: 10.1038/sj.jp.7210587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Positive Airway Pressure on Diaphragm Dimensions in Preterm Infants

Abstract: We conclude that the improvement in arterial oxygen saturation with CPAP occurred despite the presence of a shorter and a less mobile diaphragm, and that other physiological and mechanical alterations accompanying the application of CPAP offset its negative effects on diaphragm function. We speculate that with excessive CPAP, however, diaphragm dysfunction along with the previously described adverse hemodynamic effects may outweigh its benefits on oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Rehan et al. demonstrated a direct correlation between an increase in PEEP and oxygen saturation, and in the present, it was kept constant in the same infant in the different decubitus positions.…”
Section: Discussionsupporting
confidence: 57%
“…Rehan et al. demonstrated a direct correlation between an increase in PEEP and oxygen saturation, and in the present, it was kept constant in the same infant in the different decubitus positions.…”
Section: Discussionsupporting
confidence: 57%
“…This pressure helps recruit alveoli and increase functional residual lung capacity [12], thus lowering the baby's work of breathing. The result is better compliance, reduced airway resistance, conservation of surfactant, and stabilized chest and diaphragm [13]. Bubble CPAP has been used in developed countries for decades [8].…”
Section: Introductionmentioning
confidence: 99%
“…They have found that as CPAP was increased from low to high levels, diaphragm thickness increased significantly both at end-expiratory and at end-inspiratory lung volumes, whereas diaphragm excursion decreased at high level of CPAP, suggesting that the application of CPAP may impair diaphragm function. 22 No previous study has utilized ultrasonography to evaluate diaphragmatic thickness and excursion during nHFT therapy. The aim of our study is to compare the effect of nCPAP and nHFT on diaphragmatic dimensions and excursion as assessed by bedside ultrasonography in preterm infants (with gestational age of more than 27 weeks).…”
mentioning
confidence: 99%